2012
DOI: 10.1002/edn.206
|View full text |Cite
|
Sign up to set email alerts
|

Perceived knowledge about diabetes among personnel in municipal care: a qualitative focus group interview study

Abstract: The aim of this study was to explore the perceived knowledge of diabetes among personnel practising in municipal care. The study was conducted using a qualitative approach through focus group interviews. The study included focus group interviews on three occasions, with a total of 22 enrolled nurses (ENs). The results showed that the ENs' perceived knowledge of diabetes was not optimal. However, the study findings demonstrated that the ENs felt they had sufficient knowledge of nursing interventions, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In a Korean study, 80% of practice nurses scored poorly on diabetes dietary questions relating to sources of carbohydrates for diabetes patients (Park et al, 2011). A qualitative study conducted in Sweden reported that none of the 22 participating enrolled nurses could distinguish the different types of diabetes or the symptoms of diabetes (Olsen, Granath, Wharén, Blom, & Leksell, 2012). Together these findings indicate that the nursing workforces internationally may experience significant knowledge deficits across many areas of diabetes care (Alotaibi, Al-Ganmi, Gholizadeh, & ACCEPTED MANUSCRIPT…”
mentioning
confidence: 99%
“…In a Korean study, 80% of practice nurses scored poorly on diabetes dietary questions relating to sources of carbohydrates for diabetes patients (Park et al, 2011). A qualitative study conducted in Sweden reported that none of the 22 participating enrolled nurses could distinguish the different types of diabetes or the symptoms of diabetes (Olsen, Granath, Wharén, Blom, & Leksell, 2012). Together these findings indicate that the nursing workforces internationally may experience significant knowledge deficits across many areas of diabetes care (Alotaibi, Al-Ganmi, Gholizadeh, & ACCEPTED MANUSCRIPT…”
mentioning
confidence: 99%
“…Knowledge deficits in various aspects of diabetes care and management have been demonstrated for nurses working in different healthcare settings in Saudi Arabia and elsewhere [ 12 17 ]. For instance, a study showed that the perceived knowledge of Swedish nurses about caring for old patients with diabetes was not optimal, lacking the ability to distinguish diabetes types or symptoms [ 13 ]. In Saudi Arabia, a gap was found between the perceived and actual knowledge of diabetes among nurses in a tertiary care hospital, with mean scores being 46.9 (of a maximum of 60) for self-reported knowledge and 25.4 (of a maximum of 49 for actual knowledge about diabetes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the world, nurses working in a variety of healthcare settings have been shown to have knowledge deficits in all aspects of diabetes care and its management (Alotaibi, Gholizadeh, Al‐Ganmi, & Perry, ; Gerard, Griffin, & Fitzpatrick, ; Olsen, Granath, Wharén, Blom, & Leksell, ; Yacoub et al., ). A study from Saudi Arabia found that nurses had low accuracy in relation to diet/nutrition, diabetes medications, diabetes pathology, symptoms and management (Alotaibi, Gholizadeh et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A study from Saudi Arabia found that nurses had low accuracy in relation to diet/nutrition, diabetes medications, diabetes pathology, symptoms and management (Alotaibi, Gholizadeh et al., ). They are not unique in this: A Swedish study found that enrolled nurses could not distinguish the different types of diabetes or their symptoms (Olsen et al., ), and inadequate knowledge of diabetes medications was found among nurses in the United States and Jordan (Gerard et al., ; Yacoub et al., ). Nurses indicated that knowledge deficiencies resulted from barriers preventing them achieving full understanding of diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation